Factors motivating lebanese youth to adopt COVID-19 good practices: a cross-sectional study - Bou-Hamad, Imad; Hoteit, Reem (Frontiers in Public Health, 2023)
Background It is now widely acknowledged that young people can be asymptomatic carriers of the COVID-19 virus. While vaccines are successful, COVID-19 good practices continue to be useful in controlling the virus transmission. This study aimed to investigate the associated risk factors impacting the youths' adoption of COVID-19 good practices in Lebanon. Methods Data were collected through an online survey. The analyzed sample included 602 young people. Results Our results indicate that around half the youth sample in our study adhere to COVID-19 good practices. COVID-19 good practices are more likely to be adopted by individuals who are more worried about their health and those who live with their partners. Furthermore, media trust was a significant predictor of COVID-19 good practices. Conclusion Media can play a larger role in promoting good practices through youth-targeted programs. By identifying community influencers and encouraging peer-to-peer communication, it is possible to engage youth who distrust the media and persuade them to adopt COVID-19 good practices.